2020
DOI: 10.1007/s11414-019-09679-z
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Leadership Style in Behavioral Health Care: a Literature Review

Abstract: Burnout among behavioral health care providers and employees is associated with poor patient and provider outcomes. Leadership style has generally been identified as a means of reducing burnout, yet it is unclear whether some leadership styles are more effective than others at mitigating burnout. Additionally, behavioral health care is provided in a variety of contexts and a leadership style employed in one context may not be effective in another. The purpose of this paper was to review the literature on leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 67 publications
0
32
0
3
Order By: Relevance
“…Therefore, the present study contributes to the role of LMX in the wake of an extreme context, such as the COVID-19 pandemic. Further, regardless of the contextualized outlook, by acknowledging how LMX is linked to burnout among medical staff, our study addresses recent calls for research on the role of specific leadership perspectives on psychological syndromes, such as burnout and post-traumatic stress disorder (Kelly & Hearld, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the present study contributes to the role of LMX in the wake of an extreme context, such as the COVID-19 pandemic. Further, regardless of the contextualized outlook, by acknowledging how LMX is linked to burnout among medical staff, our study addresses recent calls for research on the role of specific leadership perspectives on psychological syndromes, such as burnout and post-traumatic stress disorder (Kelly & Hearld, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Apart from that, the study by Aronsson et al [ 40 ] showed that high levels of job support, workplace justice, job control, and reward helped protect against exhaustion. Further examples of stressor/demand relevant resources are self-efficacy [ 47 ], having a transformative leader at work [ 48 ], and formal education relevant for the work and position at work [ 41 ].…”
Section: A Proposed Cognitive Behavioral Explanatory Model Of Clinmentioning
confidence: 99%
“…The behaviours and leadership styles of supervisors and managers are important influences on frontline health worker mental health. 41,42 Transformational leadership behaviours (communicating a vision, motivating the group toward higher goals, encouraging creative thinking, and being considerate of individual employees), for instance, have been found to be negatively associated with stress and burnout, and positively associated with self-rated psychosocial well-being. [43][44][45][46] Transformational leadership behaviours can also decrease staff absenteeism, 47 turnover intention, 48,49 and enhance staff retention 50 -concerns currently of paramount importance as record numbers of health professionals in Canada are leaving their respective professions.…”
Section: Introductionmentioning
confidence: 99%